ANALISA TRACER STUDI PADA UNIVERSITAS XYZ - Muhammad Arifin; Syafiul Muzid (Jurnal DISPROTEK, 2018)
Tracer Study aims to obtain graduate data, conformity of knowledge and skills acquired, transition work. This activity is done as evidence of college responsibility to graduates. The method used in the tracking study consisted of four stages: (1) preparation, (2) implementation, (3) analysis and phase (4) evaluation of results. Preparation stage update graduate data, development of questionnaires, drafting and traning surveyor invitations. Implementation stage consists of the dissemination of invitations, monitoring and reminder. The analysis phase is the process of analyzing and recapitulating the questionnaire. While the evaluation phase is the overall reporting and evaluation stage of the program. Through this method it is expected that all graduates can be traced. The problems in the tracer study at XYZ University include the collection of graduate data obtained from the graduation books so that the data is not accurate, the phone numbers are many that can not be contacted or not active, the method of interview is the method of filling the questionnaire through the telephone is very effective but constrained the problem of respondent time, total respondents are still below the expected target, this is because the process is less interesting and the length of time in the process of filling questionnaires and caused because the data is less valid Keywords: Graduates, Tracer Study UMK Tracer Study bertujuan untuk mendapatkan data lulusan, kesesuaian pengetahuan dan keterampilan yang diperoleh, transisi bekerja. Kegiatan ini dilakukan sebagai bukti tanggung jawab perguruan tinggi terhadap lulusan. Metode yang digunakan dalam studi pelacakan terdiri dari empat tahap: (1) persiapan, (2) pelaksanaan, (3) analisis dan fase (4) evaluasi hasil. Tahap persiapan memperbarui data lulusan, pengembangan kuesioner, penyusunan dan traning surveyor undangan. Tahap implementasi terdiri dari penyebaran undangan, monitoring dan reminder. Tahap analisis adalah proses menganalisis dan rekapitulasi kuesioner. Sementara tahap evaluasi adalah tahap pelaporan dan evaluasi program secara keseluruhan. Melalui metode ini diharapkan semua lulusan dapat terlacak. Problem dalam studi tracer di Universitas XYZ meliputi pengumpulan data lulusan yang diperoleh dari buku-buku wisuda sehingga datanya kurang akurat, nomor telepon banyak yang tidak dapat dihubungi atau tidak aktif, metode wawancara yaitu metode pengisisan kuesioner melalui telpon sangat efektif tetapi terkendala masalah waktu responden, total responden masih dibawah target yang diharapkan, hal ini karena proses yang kurang menarik dan lamanya waktu dalam proses pengisian kuesioner serta disebabkan karena data yang kurang valid. Kata Kunci: Lulusan, Tracer Study